The Moral Case for the Legislation of Voluntary Euthanasia - Oddie, Graham (Victoria University of Wellington Law Review, 1998)
If a person is suffering from some illness or disability and wishes to end their We the law ought to facilitate rather than frustrate that choice argues Graham Oddie in this article. He points out the inconsistencies in current medical practice, and the gross disparity between the practice and the letter of the law. In dismissing many of the commonly raised objections to calls for reform of the law permitting euthanasia he makes a strong case for consistency in our approach to the right to die and patient autonomy.